2017
DOI: 10.1093/europace/euw421
|View full text |Cite
|
Sign up to set email alerts
|

Rate vs. rhythm control and adverse outcomes among European patients with atrial fibrillation

Abstract: In a European AF patients' cohort, a pure rate control strategy was associated with a higher risk for adverse events at 1-year follow-up, and partially adjusted analysis suggested that rate control independently increased the risk for all-cause death. A fully adjusted propensity score matched analysis found that this association was no longer statistically significant, suggesting an important role of comorbidities in determining the higher risk for all-cause death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
6
28
0
1
Order By: Relevance
“…Although the primary outcome of proportion of SR did not show a statistical difference between groups, our data appear to demonstrate at least equivalence with the most effective antiarrhythmic medication available in clinical studies [7–9] and improved echocardiographic parameters for both E/A ratio and LAD after berberine treatment, but only E/A ratio improved in amiodarone group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although the primary outcome of proportion of SR did not show a statistical difference between groups, our data appear to demonstrate at least equivalence with the most effective antiarrhythmic medication available in clinical studies [7–9] and improved echocardiographic parameters for both E/A ratio and LAD after berberine treatment, but only E/A ratio improved in amiodarone group.…”
Section: Discussionmentioning
confidence: 48%
“…These early data showed potential for this agent as an antiarrhythmic with only minor gastrointestinal side effects but without comparing to other antiarrhythmics. The purpose of this study was to test the efficacy of berberine in the treatment of patients with atrial fibrillation (AF) in comparison with amiodarone, a frequently prescribed and widely used Vaughn-Williams class III agent efficacious in converting AF to sinus rhythm (SR) [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Age is a powerful driver of stroke and bleeding risks, also reflecting associated comorbidities and polypharmacy. Symptom status is no guide to management, as risks associated with AF are present irrespective of whether patients are asymptomatic or not, or if a rate or rhythm control strategy was used . Of note, digoxin was commonly used in the elderly patients, and some debate is evident whether digoxin use is associated with worse outcomes in AF patients …”
Section: Discussionmentioning
confidence: 99%
“…Symptom status is no guide to management, as risks associated with AF are present irrespective of whether patients are asymptomatic or not, or if a rate or rhythm control strategy was used. 8,9 Of note, digoxin was commonly used in the elderly patients, and some debate is evident whether digoxin use is associated with worse outcomes in AF patients. 10 In the present survey, we found that the use of OAC was less likely in elderly patients with first-diagnosed AF, greater NYHA class or concomitant use antiplatelet drug therapy, whereas patients managed by a cardiologist or in an academic centre were more likely receive OAC.…”
Section: Discussionmentioning
confidence: 99%
“…Поява СЕ після тесту з фізичним наванта-женням у хворих на АГ передбачає розвиток ФП в подальшому [8]. Відомо, що у хворих на АГ ШЕ збі-льшує ризик серцевої смерті, навіть при відсутності супутньої ішемічної хвороби серця [11,13,16]. Про-те на сьогодні не виділені чіткі критерії для прогно-зування розвитку екстрасистолій у хворих АГ.…”
unclassified